High-entropy alloy structured composite negative electrode material, preparation method thereof and lithium metal battery

By introducing high-entropy alloy structured composite materials into the negative electrode material of lithium metal batteries, using its three-dimensional framework network and multiphase coexistence characteristics, the problem of SEI and lithium dendrites in the charging and discharging process of lithium batteries is solved, and the problem of instability of SEI and lithium dendrites is achieved. Longer cycle life and better rate performance.

CN119419256AInactive Publication Date: 2025-02-11MONTA VISTA ENERGY TECH CORP (ANHUI)

Patent Information

Application Number
CN202510015005.X
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2025-01-06
Publication Date
2025-02-11
Estimated Expiration
Not applicable · inactive patent

AI Technical Summary

Technical Problem

Lithium metal batteries are prone to form unstable solid electrolyte interfaces (SEIs) and lithium dendrites during charging and discharging, resulting in reduced battery coulomb efficiency, short cycle life and poor rate performance.

Method used

A structured composite anode material of high-entropy alloy is adopted, which consists of lithium, non-metallic elements and other metal elements. Through the three-dimensional framework network structure of high-entropy alloy and the multi-phase coexistence design, the mechanical properties and structural stability of the anode are enhanced.

Benefits of technology

It improves the negative electrode structure stability and local current uniformity of lithium metal batteries, extends the battery cycle life and improves the rate performance, while maintaining high Coulomb efficiency.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119419256A_ABST
    Figure CN119419256A_ABST
Patent Text Reader

Abstract

The invention discloses a high-entropy alloy structured composite negative electrode material and a preparation method thereof and a lithium metal battery, and belongs to the technical field of lithium batteries, the high-entropy alloy structured composite negative electrode material comprises lithium, non-metallic elements and other metallic elements, the ratio of lithium atoms to total atoms in the composite negative electrode material is 40-80 at%, and the ratio of non-metallic elements to total atoms in the composite negative electrode material is 1-10 at%. The ratio of atoms corresponding to the non-metallic elements to the total atoms is 1-20 at%, the balance is other metallic elements, the atomic ratio of the other metallic elements is equal, the metal lithium and compounds or simple substances of the other metallic elements are smelted to obtain high-entropy alloy liquid, the high-entropy alloy liquid is subjected to heat preservation and poured into a mold, the high-entropy alloy sheet is obtained after cooling, and the composite negative electrode material contains various eutectic phases, the internal composition segregation is weakened, the organization structure is more uniform, the distortion degree and dislocation accumulation of the alloy in the deformation process are reduced, then the effect of improving the ductility is achieved, and the commercial application of the lithium alloy negative electrode is improved.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present invention belongs to the technical field of lithium batteries, and in particular relates to a high entropy alloy structured composite negative electrode material and a preparation method thereof, and a lithium metal battery. Background Art

[0002] Lithium metal batteries have always attracted much attention among high energy density batteries. In particular, their 3860 mAh g -1 The ultra-high theoretical specific capacity and the lowest standard reduction potential (–3.040 V vs. standard hydrogen electrode, SHE) make lithium an extremely attractive anode material.

[0003] The electrolyte will be reduced by lithium metal, resulting in the formation of a solid electrolyte interface (SEI). During the charging process, the battery will form "unclaimed lithium" (i.e., lithium plating). The SEI may rupture due to mechanical instability and continuously expose new lithium metal. In this way, the exposed fresh lithium will consume the electrolyte, reduce the Coulomb efficiency of the battery, and the increase in SEI thickness will also increase the impedance of the battery. During the lithium plating process, the ruptured SEI will provide an uneven new surface, which will eventually cause the deposition process to gradually deteriorate, leading to the formation of dead lithium and dendrites. The Sand equation shows that the time for lithium dendrite formation is inversely proportional to the current density. Therefore, the uniform distribution of current is crucial to balancing the space charge and avoiding the establishment of local electric fields.

[0004] The high entropy effect is the iconic theory of high entropy alloys. This theory believes that compared with vibration entropy, electronic entropy and magnetic entropy, configuration entropy plays a dominant role in the formation of solid solutions, and high configuration entropy can promote the formation of stable solid solution phases. According to the Gibbs free energy formula, when the temperature is constant, the higher the mixing entropy in the alloy system, the more stable the system; the degree of lattice distortion of the solid solution formed by high entropy alloys is significantly greater than that of metal single substances and binary alloy systems. This large lattice distortion field will also hinder the movement of atoms and the slip of dislocations, enhancing the solid solution strengthening effect. This structure will also affect the physical properties of the alloy, such as electrical conductivity and thermal conductivity; in high entropy alloys, the diffusion of atoms is considered to be slow, and atoms are more difficult to diffuse in high entropy alloy systems. This structural stability has great potential for application in high temperature fields. It is of great help to the thermal stability of batteries; there is a cocktail effect in high entropy alloys, that is, the alloy performance formed by the combination of multiple elements may be greater than the sum of the performance of individual elements, that is, excellent material properties often come from the synergy between a large number of different elements.

[0005] In summary, high-entropy alloy structured composite anode can enhance mechanical properties and structural stability through lattice distortion.

[0006] The high-entropy alloy structured composite negative electrode system has good stability, forms a stable SEI layer, and the local current is evenly distributed, which greatly improves the battery cycle life. Summary of the invention

[0007] The purpose of the present invention is to provide a high entropy alloy structured composite negative electrode material to improve the structural stability of the negative electrode of a lithium metal battery, improve the local current uniformity stability and mechanical properties, and aim to improve the cycle life and rate performance of the lithium metal battery.

[0008] The purpose of the present invention can be achieved by the following technical solutions: A high entropy alloy structured composite negative electrode material comprises lithium, non-metallic elements and other metal elements, wherein the other metal elements are at least three of Mg, Zn, Ca, Sn, Al, Ag, Pt, Cu, Au and lanthanide elements; and the non-metallic element is at least one of F, N, Si, B, S, P, H, O and C.

[0009] Furthermore, the ratio of lithium atoms to total atoms in the composite negative electrode material is 40at%-80at%.

[0010] Furthermore, the ratio of atoms corresponding to non-metallic elements to total atoms is 1at%-20at%, and the remainder is the atomic ratio corresponding to other metal elements and the atomic ratio of other metal elements.

[0011] Furthermore, the thickness of the high entropy alloy structured composite negative electrode material is 20-100 μm.

[0012] Furthermore, the high entropy alloy structured composite negative electrode material contains a multiphase structure of various lithium alloy phases, constituting a three-dimensional skeleton network structure of the high entropy alloy structured composite negative electrode material.

[0013] A method for preparing a high entropy alloy structured composite negative electrode material comprises the following steps: Compounds or single substances of other metal elements and lithium are melted to obtain high entropy alloy liquid, which is kept warm and poured into a mold. After cooling, a high entropy alloy sheet is obtained. Compounds or single substances containing non-metallic elements are roll-pressed with the high entropy alloy sheet to obtain a high entropy alloy structured composite negative electrode material.

[0014] Furthermore, the smelting temperature is 200-1200° C. and the insulation time is 0.5-10 h.

[0015] Furthermore, pouring into a mold means pouring into a mold with cooling water circulating therethrough to cool down to 300-500° C., and then rapidly cooling to obtain a high entropy alloy sheet.

[0016] Furthermore, the rapid cooling rate is 5-1000°C / s, cooling to 25-75°C.

[0017] A lithium metal battery comprises the above-mentioned high entropy alloy structured composite negative electrode material.

[0018] Beneficial effects of the present invention: First, the three-dimensional skeleton electrode material in the present invention can slow down the formation of lithium dendrites and lead to a highly stable and reversible lithium metal plating-stripping cycle with high coulombic efficiency, while the nanostructure and self-supporting main structure increase the active surface area and provide an effective accommodation space for the deposited lithium metal.

[0019] Second, the lithium in the present invention accounts for a high proportion of the alloy components, which replenishes the consumed lithium in the charge and discharge cycle, improves the coulombic efficiency, and improves the electrochemical performance of the high entropy alloy structured composite negative electrode material. According to the Gibbs free energy formula, when the temperature is constant, the higher the mixing entropy in the alloy system, the more stable the system is. At the same time, the diffusion of atoms is considered to be slow, and atoms are more difficult to diffuse in the high entropy alloy system. The high entropy alloy structured composite negative electrode material in the present invention can keep the negative electrode material stable in long-term cycles regardless of high or low temperatures.

[0020] Third, the high entropy alloy structured composite negative electrode material of the present invention contains a variety of eutectic phases, the internal component segregation is weakened, the organizational structure is more uniform, and the degree of distortion and dislocation accumulation of the alloy during deformation is reduced, thereby achieving the effect of improving ductility. Compared with pure lithium, it has better machinability and improves the commercial application of lithium alloy negative electrode materials. BRIEF DESCRIPTION OF THE DRAWINGS

[0021] The present invention will be further described below in conjunction with the accompanying drawings.

[0022] Figure 1 This is a macroscopic picture of the high entropy alloy structured composite negative electrode material in Example 1 of the present invention; Figure 2 is a cross-sectional SEM image of the high entropy lithium alloy in Example 1 of the present invention; Figure 3 This is a comparison diagram of the interface impedance of Examples 1 to 3 and Comparative Example 1 after charge and discharge cycles in an electrolyte; Figure 4 It is a comparison chart of the coulombic efficiency of Examples 1-3 and Comparative Example 1; Figure 5 A comparison chart of the discharge specific capacity between Examples 1-3 and Comparative Example 1; Figure 6 Schematic diagram of the three-dimensional high entropy alloy skeleton in Example 4. DETAILED DESCRIPTION

[0023] The following will be combined with the embodiments of the present invention to clearly and completely describe the technical solutions in the embodiments of the present invention. Obviously, the described embodiments are only part of the embodiments of the present invention, not all of the embodiments. Based on the embodiments of the present invention, all other embodiments obtained by ordinary technicians in this field without creative work are within the scope of protection of the present invention.

[0024] Example 1

[0025] A preferred embodiment of the present invention provides a method for preparing a high entropy lithium aluminum silver lanthanum carbon hydrogen fluorine nitrogen alloy structured composite negative electrode material containing a three-dimensional skeleton network, and the specific steps are as follows: Metal lithium, aluminum, silver, and lanthanum are placed in a crucible at an atomic ratio of 50:10:10:10. In an argon atmosphere, induction heating is used to heat the liquid until it is completely melted and turns bright orange-red. The temperature is about 1000°C, and the alloy is kept at this temperature for 0.5h. Then, it is introduced into a copper mold (the copper mold contains a cooling water circulation). When the temperature drops to 350°C, the cooling water circulation is turned on and it is quickly cooled to room temperature. The lithium aluminum silver lanthanum alloy is placed in a roller press and rolled into a sheet. The flaky lithium aluminum silver lanthanum alloy is then used to wrap the hard carbon and ammonium fluoride powders. The flaky high entropy lithium aluminum silver lanthanum alloy, hard carbon material, and ammonium fluoride powder are in a certain mass ratio to obtain Li 50 Al 10 Ag 10 La 10 The alloy of C8H8F2N2 was rolled to 100 μm high entropy lithium aluminum silver lanthanum carbon hydrogen fluorine nitrogen alloy negative electrode material. The negative electrode sheet was photographed and subjected to scanning electron microscopy. The results are shown in Figure 1 and Figure 2 .

[0026] The alloy negative electrode material was cut into 55×81 mm negative electrode sheets, and a soft-pack battery was used. In an ester electrolyte (1M LiPF6in DEC:EC=1:1 Vol% commercial electrolyte (LB-008)), a Celgard 2325 separator and NCM811 were used to assemble a 3.5 Ah soft-pack battery for cycle testing and impedance testing. The results are shown in Figure 3-Figure 5 and Table 1.

[0027] Example 2

[0028] The preferred embodiment of the present invention provides a method for preparing a high entropy lithium-magnesium-copper-platinum-boron-fluorine alloy structured composite negative electrode material containing a three-dimensional skeleton network, and the specific steps are as follows: Metal lithium, magnesium, copper, and platinum are placed in a crucible at an atomic ratio of 80:5:5:5. In an argon atmosphere, induction heating is used to heat the liquid until it is completely melted and turns bright orange-red. The temperature is about 1000 °C, and the alloy is kept at this temperature for 1 hour. Then, it is introduced into a copper mold (the copper mold contains a cooling water circulation). When the temperature drops to 300 °C, the cooling water circulation is turned on and it is quickly cooled to room temperature. The lithium-magnesium-copper-platinum alloy is placed in a roller press and rolled into a sheet. The boron trifluoride powder is then wrapped with the flaky lithium-magnesium-copper-platinum alloy, wherein the flaky high-entropy lithium-magnesium-copper-platinum alloy and the boron trifluoride powder are wrapped in a certain mass ratio to obtain Li 80 Mg5Cu5Pt5B 1.25 F 3.75 The wrapped alloy is rolled to produce a high-entropy lithium-magnesium-copper-platinum-boron-fluorine alloy negative electrode material of 100 μm.

[0029] The alloy negative electrode material was cut into 55×81 mm negative electrode sheets, and a soft-pack battery was used. In an ester electrolyte (1M LiPF6in DEC:EC=1:1 Vol% commercial electrolyte (LB-008)), a Celgard 2325 separator and NCM811 were used to assemble a 3.5 Ah soft-pack battery for cycle testing and impedance testing. The results are shown in Figure 3-Figure 5 and Table 1.

[0030] Example 3

[0031] The preferred embodiment of the present invention provides a method for preparing a high entropy lithium-tin-zinc-magnesium-nitrogen-boron-silicon alloy structured composite negative electrode material containing a three-dimensional skeleton network, and the specific steps are as follows: Metal lithium, tin and zinc are placed in a crucible with an atomic ratio of 50:10:10. In an argon atmosphere, induction heating is used to heat the liquid until it is completely melted and turns bright orange-red. The temperature is about 1200 °C, and the alloy is kept at this temperature for 2 hours. Then, it is introduced into a copper mold (the copper mold contains a cooling water circulation). When the temperature drops to 400 °C, the cooling water circulation is turned on and it is quickly cooled to room temperature. The lithium tin zinc alloy is placed in a roller press and rolled into a sheet. Then, the magnesium diboride, magnesium nitride and silicon powder are wrapped with the alloy. The sheet-like lithium tin zinc gold alloy, magnesium diboride, magnesium nitride powder and silicon are wrapped in a certain mass ratio to obtain Li 50 Sn 10 Zn 10 Mg 10 Si 12 N6B2 alloy, and the wrapped alloy is rolled to 100 μm high entropy lithium tin zinc magnesium nitrogen boron silicon alloy negative electrode material.

[0032] The alloy negative electrode material was cut into 55×81 mm negative electrode sheets, and a soft-pack battery was used. In an ester electrolyte (1M LiPF6in DEC:EC=1:1 Vol% commercial electrolyte (LB-008)), a Celgard 2325 separator and NCM811 were used to assemble a 3.5 Ah soft-pack battery for cycle testing and impedance testing. The results are shown in Figure 3-Figure 5 and Table 1.

[0033] Example 4

[0034] The preferred embodiment of the present invention provides a method for preparing a high entropy lithium-tin-calcium-cerium-magnesium-fluorine alloy structured composite negative electrode material containing a three-dimensional skeleton network, and the specific steps are as follows: Metal lithium, tin, cerium, calcium, and magnesium are placed in a crucible at an atomic ratio of 50:10:10:10:10. In an argon atmosphere, induction heating is used to heat the liquid until it is completely melted and turns bright orange-red. The temperature is about 1200°C, and the alloy is kept at this temperature for 2 hours. Then, it is introduced into a copper mold (the copper mold contains a cooling water circulation). When the temperature drops to 400°C, the cooling water circulation is turned on and it is quickly cooled to room temperature. The lithium tin calcium cerium magnesium alloy is placed in a roller press and rolled until it is in sheet form. The lithium fluoride powder is then wrapped with the sheet-like lithium tin calcium cerium magnesium alloy, wherein the sheet-like lithium tin calcium cerium alloy and lithium fluoride are wrapped in a certain mass ratio to obtain Li 55 Sn 10 Ce 10 Ca 10 Mg 10 F5 alloy, the wrapped alloy is rolled to 100 μm high entropy lithium tin calcium cerium fluoride alloy negative electrode material.

[0035] The alloy negative electrode material was cut into 55×81 mm negative electrode sheets and assembled into 3.5 Ah soft pack batteries in an ester electrolyte (1M LiPF6in DEC:EC=1:1 Vol% commercial electrolyte (LB-008)) with Celgard 2325 separator and NCM811 for cycle testing. The results are shown in Table 1. The schematic diagram of the three-dimensional high entropy alloy skeleton is shown in Figure 6 shown.

[0036] Example 5

[0037] The preferred embodiment of the present invention provides a method for preparing a high entropy lithium silver platinum carbon silicon alloy structured composite negative electrode material containing a three-dimensional skeleton network, and the specific steps are as follows: Metal lithium, silver, platinum, and gold are placed in a crucible at an atomic ratio of 40:15:15:15. In an argon atmosphere, induction heating is used to heat the liquid until it is completely melted and turns bright orange-red. The temperature is about 1000 °C, and the alloy is kept at this temperature for 1 hour. Then, it is introduced into a copper mold (the copper mold contains a cooling water circulation). When the temperature drops to 350 °C, the cooling water circulation is turned on and it is quickly cooled to room temperature. The lithium silver platinum gold alloy is placed in a roller press and rolled until it is in sheet form. The silicon and carbon powders are then wrapped with the sheet lithium silver platinum gold alloy, wherein the sheet lithium silver platinum gold alloy, carbon and silicon are wrapped in a certain mass ratio to obtain Li 40 Ag 15 Pt 15 Au 15 C 10 Si5 alloy, the wrapped alloy is rolled to 100 μm high entropy lithium silver platinum carbon silicon alloy negative electrode material.

[0038] The alloy negative electrode material was cut into 55×81 mm negative electrode sheets and assembled into 3.5 Ah soft-pack batteries in an ester electrolyte (1M LiPF6in DEC:EC=1:1 Vol% commercial electrolyte (LB-008)) with Celgard 2325 separator and NCM811 for cycle testing. The results are shown in Table 1.

[0039] Example 6

[0040] The preferred embodiment of the present invention provides a method for preparing a high entropy lithium zinc magnesium silver cerium oxygen nitrogen hydrogen sulfur alloy structured composite negative electrode material containing a three-dimensional skeleton network, and the specific steps are as follows: Metal lithium, zinc, magnesium, silver, and cerium are placed in a crucible at an atomic ratio of 40:10:10:10:10. In an argon atmosphere, induction heating is used to heat the liquid until it is completely melted and turns bright orange-red. The temperature is about 1000 °C, and the alloy is kept at this temperature for 1 hour. Then, it is introduced into a copper mold (the copper mold contains a cooling water circulation). When the temperature drops to 300 °C, the cooling water circulation is turned on and it is quickly cooled to room temperature. The lithium zinc magnesium silver cerium alloy is placed in a roller press and rolled until it is in sheet form. The hydroxylamine sulfate powder is then coated with the flaky lithium zinc magnesium silver cerium alloy, wherein the flaky lithium zinc magnesium and hydroxylamine sulfate are coated in a certain mass ratio to obtain Li 40 Zn 10 Mg 10 Ag 10 Ce 10 (H8O6N2S) 1.18 The wrapped alloy is rolled to produce a high-entropy lithium zinc magnesium silver cerium oxygen nitrogen hydrogen sulfur alloy negative electrode material of 100 μm.

[0041] The alloy negative electrode material was cut into 55×81 mm negative electrode sheets and assembled into 3.5 Ah soft-pack batteries in an ester electrolyte (1M LiPF6in DEC:EC=1:1 Vol% commercial electrolyte (LB-008)) with Celgard 2325 separator and NCM811 for cycle testing. The results are shown in Table 1.

[0042] Example 7

[0043] The preferred embodiment of the present invention provides a method for preparing a high entropy lithium silver calcium copper aluminum tin lanthanum carbon hydrogen nitrogen sulfur alloy structured composite negative electrode material containing a three-dimensional skeleton network, and the specific steps are as follows: Metal lithium, silver, calcium, copper, aluminum, tin, and lanthanum are placed in a crucible at an atomic ratio of 50:5:5:5:5:5:5. In an argon atmosphere, induction heating is used to heat the liquid until it is completely melted and turns bright orange-red. The temperature is about 1000 °C, and the alloy is kept at this temperature for 1 hour. Then, it is introduced into a copper mold (the copper mold contains a cooling water circulation). When the temperature drops to 350 °C, the cooling water circulation is turned on and it is quickly cooled to room temperature. The lithium silver calcium copper aluminum tin lanthanum alloy is placed in a roller press and rolled into a sheet. Then, the flaky lithium silver calcium copper aluminum tin lanthanum alloy is used to wrap the trithiocyanate powder, wherein the flaky lithium silver calcium copper aluminum tin lanthanum and trithiocyanate are wrapped in a certain mass ratio to obtain Li 50 The alloy of Ag5Ca5Cu5Al5Sn5La5C5H5N5S5 is rolled to form a high-entropy lithium silver calcium copper aluminum tin lanthanum carbon hydrogen nitrogen sulfur alloy negative electrode material with a thickness of 100 μm.

[0044] The alloy negative electrode material was cut into 55×81 mm negative electrode sheets and assembled into 3.5 Ah soft-pack batteries in an ester electrolyte (1M LiPF6in DEC:EC=1:1 Vol% commercial electrolyte (LB-008)) with Celgard 2325 separator and NCM811 for cycle testing. The results are shown in Table 1.

[0045] Example 8

[0046] A preferred embodiment of the present invention provides a method for preparing a high entropy lithium zinc silver tin lanthanum phosphorus boron structured composite negative electrode material containing a three-dimensional skeleton network, and the specific steps are as follows: Metal lithium, zinc, silver, tin, and lanthanum are placed in a crucible at an atomic ratio of 48:10:10:10:10. In an argon atmosphere, induction heating is used to heat the liquid until it is completely melted and turns bright orange-red. The temperature is about 1100 °C, and the alloy is kept at this temperature for 1 hour. Then, it is introduced into a copper mold (the copper mold contains a cooling water circulation). When the temperature drops to 350 °C, the cooling water circulation is turned on and it is quickly cooled to room temperature. The lithium zinc silver tin lanthanum alloy is placed in a roller press and rolled into a sheet. Then, the flaky lithium zinc silver tin lanthanum alloy is used to wrap the boron phosphorus. The flaky lithium silver calcium copper aluminum tin lanthanum and the boron phosphorus are wrapped in a certain mass ratio to obtain Li 48 Zn 10 Ag 10 Sn 10 La 10 The B6P6 alloy is rolled to form a high-entropy lithium zinc silver tin lanthanum phosphorus boron alloy negative electrode material with a thickness of 100 μm.

[0047] The alloy negative electrode material was cut into 55×81 mm negative electrode sheets and assembled into 3.5 Ah soft-pack batteries in an ester electrolyte (1M LiPF6in DEC:EC=1:1 Vol% commercial electrolyte (LB-008)) with Celgard 2325 separator and NCM811 for cycle testing. The results are shown in Table 1.

[0048] Comparative Example 1 The battery was prepared using 100 μm pure lithium sheets, the negative electrode was cut into 55×81 mm negative electrode sheets, and a soft-pack battery was used. In an ester electrolyte (1M LiPF6 in DEC:EC=1:1 Vol% commercial electrolyte (LB-008)), a Celgard2325 separator and NCM811 were used to assemble a 3.5 Ah soft-pack battery for cycle testing and impedance testing. The results are shown in Figure 3-Figure 5 and Table 1.

[0049] Comparative Example 2 A preferred embodiment of the present invention provides a method for preparing a high entropy lithium aluminum silver lanthanum carbon hydrogen fluorine nitrogen alloy structured composite negative electrode material containing a three-dimensional skeleton network, and the specific steps are as follows: Metal lithium, aluminum, silver, and lanthanum are placed in a crucible at an atomic ratio of 50:10:10:10. In an argon atmosphere, induction heating is used to heat the liquid until it is completely melted and turns bright orange-red. The temperature is about 1000°C, and the alloy is kept at this temperature for 0.5h. Then, it is introduced into a copper mold (the copper mold contains a cooling water circulation). When the temperature drops to 350°C, the cooling water circulation is not turned on and it is slowly cooled to room temperature. The lithium aluminum silver lanthanum alloy is placed in a roller press and rolled into a sheet. The flaky lithium aluminum silver lanthanum alloy is then used to wrap the hard carbon and ammonium fluoride powders. The flaky high entropy lithium aluminum silver lanthanum alloy, hard carbon material, and ammonium fluoride powder are in a certain mass ratio to obtain Li 50 Al 10 Ag 10 La 10 C8H8F2N2 alloy, and the wrapped alloy is rolled to 100 μm high entropy lithium aluminum silver lanthanum carbon hydrogen fluorine nitrogen alloy negative electrode material.

[0050] The battery was prepared using a 100 μm high-entropy lithium aluminum silver lanthanum carbon hydrogen fluorine nitrogen alloy negative electrode. The negative electrode material was cut into 55×81mm negative electrode sheets. A soft-pack battery was used in an ester electrolyte (1M LiPF6 in DEC:EC=1:1 Vol% commercial electrolyte (LB-008)), with a Celgard 2325 model separator and NCM811, to assemble a 3.5 Ah soft-pack battery for cycle testing.

[0051] Comparative Example 3 A preferred embodiment of the present invention provides a method for preparing a high entropy lithium aluminum silver lanthanum carbon hydrogen fluorine nitrogen alloy structured composite negative electrode material containing a three-dimensional skeleton network, and the specific steps are as follows: Metal lithium, aluminum, silver, and lanthanum are placed in a crucible at an atomic ratio of 50:10:10:10. In an argon atmosphere, induction heating is used to heat the liquid until it is completely melted and turns bright orange-red. The temperature is about 1000°C, and the alloy is kept at this temperature for 0.5h. Then, it is introduced into a copper mold (the copper mold contains a cooling water circulation). When the temperature drops to 350°C, the cooling water circulation is turned on and it is quickly cooled to room temperature. The lithium aluminum silver lanthanum alloy is placed in a roller press and rolled into a sheet. The flaky lithium aluminum silver lanthanum alloy is then used to wrap the hard carbon and ammonium fluoride powders. The flaky high entropy lithium aluminum silver lanthanum alloy, hard carbon material, and ammonium fluoride powder are in a certain mass ratio to obtain Li 50 Al 10 Ag 10 La 10 C8H8F2N2 alloy, and the wrapped alloy is rolled to 120 μm high entropy lithium aluminum silver lanthanum carbon hydrogen fluorine nitrogen alloy negative electrode material.

[0052] The battery was prepared using a 120 μm high-entropy lithium aluminum silver lanthanum carbon hydrogen fluorine nitrogen alloy negative electrode. The negative electrode material was cut into 55×81mm negative electrode sheets. A soft-pack battery was used in an ester electrolyte (1M LiPF6 in DEC:EC=1:1 Vol% commercial electrolyte (LB-008)), with Celgard 2325 model separator and NCM811, to assemble a 3.5 Ah soft-pack battery for cycle testing.

[0053] Comparative Example 4 A preferred embodiment of the present invention provides a method for preparing a high entropy lithium aluminum silver lanthanum carbon hydrogen fluorine nitrogen alloy structured composite negative electrode material containing a three-dimensional skeleton network, and the specific steps are as follows: Metal lithium, aluminum, silver, and lanthanum are placed in a crucible at an atomic ratio of 50:10:10:10. In an argon atmosphere, induction heating is used to heat the liquid until it is completely melted and turns bright orange-red. The temperature is about 1000°C, and the alloy is kept at this temperature for 0.5h. Then, it is introduced into a copper mold (the copper mold contains a cooling water circulation). When the temperature drops to 350°C, the cooling water circulation is turned on and it is quickly cooled to room temperature. The lithium aluminum silver lanthanum alloy is placed in a roller press and rolled into a sheet. The flaky lithium aluminum silver lanthanum alloy is then used to wrap the hard carbon and ammonium fluoride powders. The flaky high entropy lithium aluminum silver lanthanum alloy, hard carbon material, and ammonium fluoride powder are in a certain mass ratio to obtain Li 50 Al 10 Ag 10 La 10 C8H8F2N2 alloy, and the wrapped alloy is rolled to 80 μm high entropy lithium aluminum silver lanthanum carbon hydrogen fluorine nitrogen alloy negative electrode material.

[0054] The battery was prepared using a 80 μm high-entropy lithium aluminum silver lanthanum carbon hydrogen fluorine nitrogen alloy negative electrode. The negative electrode material was cut into 55×81mm negative electrode sheets. A soft-pack battery was used in an ester electrolyte (1M LiPF6 in DEC:EC=1:1 Vol% commercial electrolyte (LB-008)), with Celgard 2325 model separator and NCM811, to assemble a 3.5 Ah soft-pack battery for cycle testing.

[0055] Comparative Example 5 A preferred embodiment of the present invention provides a method for preparing a high entropy lithium aluminum silver lanthanum carbon hydrogen fluorine nitrogen alloy structured composite negative electrode material containing a three-dimensional skeleton network, and the specific steps are as follows: Metal lithium, aluminum, silver, and lanthanum are placed in a crucible at an atomic ratio of 50:5:15:10. In an argon atmosphere, induction heating is used to heat the liquid until it is completely melted and turns bright orange-red. The temperature is about 1000°C, and the alloy is kept at this temperature for 0.5 hours. Then, it is introduced into a copper mold (the copper mold contains a cooling water circulation). When the temperature drops to 350°C, the cooling water circulation is turned on and it is quickly cooled to room temperature. The lithium aluminum silver lanthanum alloy is placed in a roller press and rolled into a sheet. The flaky lithium aluminum silver lanthanum alloy is then used to wrap the hard carbon and ammonium fluoride powders. The flaky high entropy lithium aluminum silver lanthanum alloy, hard carbon material, and ammonium fluoride powder are in a certain mass ratio to obtain Li 50 Al5Ag 15 La 10 C8H8F2N2 alloy, and the wrapped alloy is rolled to 100 μm high entropy lithium aluminum silver lanthanum carbon hydrogen fluorine nitrogen alloy negative electrode material.

[0056] The battery was prepared using a 100 μm high-entropy lithium aluminum silver lanthanum carbon hydrogen fluorine nitrogen alloy negative electrode. The negative electrode material was cut into 55×81mm negative electrode sheets. A soft-pack battery was used in an ester electrolyte (1M LiPF6 in DEC:EC=1:1 Vol% commercial electrolyte (LB-008)), with a Celgard 2325 model separator and NCM811, to assemble a 3.5 Ah soft-pack battery for cycle testing.

[0057] Figure 1 This is an optical photograph of the high-entropy alloy structured composite negative electrode material synthesized in Example 1 of the present invention. The color is light yellow, which is different from the bright white pure lithium. This is because lithium undergoes an alloying reaction with other metal elements and is doped and rolled with non-metallic elements, resulting in a rough surface.

[0058] Figure 2 This is a cross-sectional scanning electron microscope image of the high entropy alloy structured composite negative electrode material in Example 1 of the present invention. From the electron microscope photo, it can be seen that the compound added by rolling in the cross section is evenly distributed inside the high entropy alloy structured composite negative electrode material. The compound increases the lithium affinity of the negative electrode material, which is beneficial to promote the rapid transport of lithium ions along the skeleton. At the same time, the three-dimensional skeleton of the high entropy alloy structured composite negative electrode with multi-phase coexistence and the presence of evenly distributed compounds around the skeleton enhance the mechanical strength of the negative electrode.

[0059] Figure 3 The impedance data of each embodiment and comparative example after 3 cycles of 0.1 C are tested. The impedance of embodiment 1, embodiment 2 and embodiment 3 are significantly lower than that of comparative example 1, indicating that embodiment 1, embodiment 2 and embodiment 3 can effectively inhibit the interface side reaction and promote the uniform deposition of lithium; and, compared with the pure lithium negative electrode, the electrode of the high entropy alloy structured composite negative electrode is more conducive to lithium ion transmission.

[0060] Figure 4-Figure 5 In the 0.2 C charging and 0.5 C discharging cycle data, the capacity of the pure lithium negative electrode battery decayed rapidly after 90 cycles, and finally cycled 113 cycles. All embodiments slowly decreased, and finally embodiment 1 cycled 175 cycles, embodiment 2 cycled 186 cycles, and embodiment 3 cycled 182 cycles, all showing longer cycle life than comparative example 1. At the same time, during the cycle process, the coulomb efficiency was maintained at about 100%, showing good cycle stability. Obviously, the comparative test results show that the high entropy alloy structured composite negative electrode has better electrochemical performance than the pure lithium negative electrode.

[0061] Table 1

[0062] The results in Table 1 show that through the design of this high entropy alloy structured composite negative electrode, an alloy negative electrode with high configuration entropy, three-dimensional skeleton structure and uniformly distributed compounds can be designed. Compared with pure lithium negative electrode, the alloy negative electrode improves structural entropy, lithium affinity, reduces volume expansion, enhances the mechanical strength of the negative electrode, and increases the cycle life by 100%. It greatly improves the application of lithium metal batteries.

[0063] It should be noted that, in this article, relational terms such as first and second, etc. are only used to distinguish one entity or operation from another entity or operation, and do not necessarily require or imply any such actual relationship or order between these entities or operations. Moreover, the terms "include", "comprise" or any other variants thereof are intended to cover non-exclusive inclusion, so that a process, method, article or device including a series of elements includes not only those elements, but also other elements not explicitly listed, or also includes elements inherent to such process, method, article or device.

[0064] Although embodiments of the present invention have been shown and described, it will be appreciated by those skilled in the art that various changes, modifications, substitutions and variations may be made to the embodiments without departing from the principles and spirit of the present invention, and that the scope of the present invention is defined by the appended claims and their equivalents.

Claims

1. A high entropy alloy structured composite negative electrode material, characterized in that: It includes lithium, non-metallic elements and other metal elements, wherein the other metal elements are at least three of Mg, Zn, Ca, Sn, Al, Ag, Pt, Cu, Au and lanthanide elements; and the non-metallic element is at least one of F, N, Si, B, S, P, H, O and C.

2. A high entropy alloy structured composite negative electrode material according to claim 1, characterized in that: The ratio of lithium atoms to total atoms in the composite negative electrode material is 40at%-80at%.

3. A high entropy alloy structured composite negative electrode material according to claim 2, characterized in that: The atoms corresponding to non-metallic elements account for 1at%-20at% of the total atoms, and the remainder is the atomic ratio corresponding to other metal elements and the equal atomic ratio of other metal elements.

4. The high entropy alloy structured composite negative electrode material according to claim 1, characterized in that: The thickness of the high entropy alloy structured composite negative electrode material is 20-100 μm.

5. The high entropy alloy structured composite negative electrode material according to claim 1, characterized in that: The high entropy alloy structured composite negative electrode material contains a multiphase structure of a lithium alloy phase, which constitutes a three-dimensional skeleton network structure of the high entropy alloy structured composite negative electrode material.

6. A method for preparing a high entropy alloy structured composite negative electrode material according to any one of claims 1 to 5, characterized in that: The steps include: Compounds or single substances of other metal elements and lithium are melted to obtain high entropy alloy liquid, which is kept warm and poured into a mold. After cooling, a high entropy alloy sheet is obtained. Compounds or single substances containing non-metallic elements are roll-pressed with the high entropy alloy sheet to obtain a high entropy alloy structured composite negative electrode material.

7. The method for preparing a high entropy alloy structured composite negative electrode material according to claim 6, characterized in that: The smelting temperature is 200-1200° C. and the insulation time is 0.5-10 h.

8. The method for preparing a high entropy alloy structured composite negative electrode material according to claim 6, characterized in that: Pouring into a mold means pouring into a mold with cooling water circulating therethrough to cool the material to 300-500° C., and then rapidly cooling the material to obtain a high entropy alloy sheet.

9. The method for preparing a high entropy alloy structured composite negative electrode material according to claim 8, characterized in that: The rapid cooling rate is 5-1000°C / s, cooling to 25-75°C.

10. A lithium metal battery, characterized in that: The invention comprises the high entropy alloy structured composite negative electrode material as described in any one of claims 1 to 5.

Citation Information

Patent Citations

  • Multi-component composite alloy negative electrode material and preparation method thereof

    CN111755662A

  • High-entropy lithium alloy negative electrode and preparation method thereof

    CN115986064A

  • Method for preparing tin / lithium disulfide composite negative electrode through combination of melting and mechanical rolling

    CN117253967A

  • Method for preparing composite metal lithium negative electrode and lithium ion battery

    CN118213484A

  • Boron-containing composite lithium metal negative electrode material as well as preparation method and application thereof

    CN118367135A

Cited By

  • High-entropy alloy pole piece and preparation method and application thereof

    CN120878756A